2007
DOI: 10.1111/j.1747-0765.2007.00110.x
|View full text |Cite
|
Sign up to set email alerts
|

Succession and phylogenetic composition of eubacterial communities in rice straw during decomposition on the surface of paddy field soil

Abstract: To estimate the bacterial communities in rice straw left on the soil surface of paddy fields, polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE) analysis was conducted. Rice straw samples were placed on the soil surface in a Japanese paddy field under drained conditions after harvest and under flooded conditions after the transplanting of rice. The residual samples on the soil surface under upland conditions were collected just before spring plowing and were replaced again on the soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…The rice field was located at Anjo Research and Extension Center in Japan, and experiment set‐up has been described in detail by Asari and colleagues (2007). Briefly, during the flooding period aerobic surface soil and the sheath part of rice straw in the surface layer of the rice field were collected in triplicate.…”
Section: Resultsmentioning
confidence: 99%
“…The rice field was located at Anjo Research and Extension Center in Japan, and experiment set‐up has been described in detail by Asari and colleagues (2007). Briefly, during the flooding period aerobic surface soil and the sheath part of rice straw in the surface layer of the rice field were collected in triplicate.…”
Section: Resultsmentioning
confidence: 99%
“…In our recent study, dried rice callus labelled with 13 C was used as a model of plant residue to trace the incorporation of callus‐derived carbon into bacteria in a rice field soil under drained conditions through DNA‐SIP (Lee et al ., ). Results demonstrated that the bacterial community incorporating callus carbon was more diverse than expected from the results of the previous studies on the bacterial community inhabiting plant residues (Sugano et al ., ; Asari et al ., ; Matsuyama et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Phospholipid fatty acids (PLFAs) profiling revealed the seasonal change in the bacterial community structure and fungal biomass of rice straw in a rice field (Nakamura et al ., ). Nucleic acid‐based analysis gave detailed phylogenetic information of the microbial community inhabiting plant residues (Weber et al ., , b; Sugano et al ., , b, ; Asari et al ., ). Comparison of the results from different microbial habitats in a rice field demonstrated that the microbial community of plant residues in rice field soil is distinct from that of the bulk soil (Kimura & Asakawa, ; Asakawa & Kimura, ).…”
Section: Introductionmentioning
confidence: 99%
“…Floodwater is a complex habitat where organic matter is produced by algae and phytoplankton, with the contribution of floating weeds, and where microorganisms promote different catabolic processes (Asari et al 2007;Kimura et al 2002;Nakayama et al 2006). When compared with other natural aquatic environments, the floodwater ecosystem is unstable, being presumably affected by an interrelated set of factors (Shibagaki-Shimizu et al 2006).…”
Section: Introductionmentioning
confidence: 99%